Flight characteristics and mutual interference analysis of projectile launched in parallel. Issue 1 (January 2021) - Zhu, W F; Zhao, N; Qu, J; Wang, Y W
Abstract: Using the knowledge of computational fluid dynamics, a 3D simulation model of a 16 tube gun was established, and the process of muzzle flow field from single formation to mutual interference, stability and attenuation was simulated by solving N-S equations. Through the simulation analysis, it can be seen that the muzzle flow field formed by each barrel will influence and superpose each other when the multi-barrel gun is launched, and the lateral force caused by the asymmetric muzzle blast wave is acted on the projectile, and the lateral force of the middle four projectiles is small, the other 12 projectiles is larger. The results can be used as a reference for structural design, firing accuracy prediction and muzzle parameters test of multi-barrel launching weapon system.